Analysis Young Driver Behavior in “Z” Generation - Khusnul Khotimah; Yogi Arisandi (Syntax Corporation Indonesia, 2020)
The magnitude of the cause of the accident due to driver error causes the need to do an analysis related to the characteristics of the driver and the factors that most influence the cause of the accident and then the road. At this time the young driver is in generation Z who has an age between 16-21 years. Then an analysis of the characteristics of the causes of traffic accidents, especially in the